Association between mental health and sleep quality in peripheral artery disease patients: a longitudinal study - Souza, Allana Andrade (2022)
Objective: To analyze the longitudinal association between mental health and sleep quality in peripheral artery disease (PAD) patients in two periods of the COVID-19 pandemic. Methods: In this longitudinal study, 99 PAD patients were evaluated in two years of COVID-19 pandemic (2020 and 2021). Patients were interviewed by telephone call, and information regarding mental health (anxiety, unhappiness, stress and depression) and sleep quality (sleep change, difficulty to sleep and sleep improvement) were obtained. Patients were divided into: no symptoms (patients that reported no mental health symptoms, n=31, 68.2±9.4 y.o.) and one or more symptoms (patients with at least one mental health symptom, n=68, 68.1±9.4 y.o.). Results: In 2020, mental health symptoms were associated with sleep change (OR=5.018; p=0.020), difficulty to sleep (OR=12.250; p=0.003) and sleep improvement (OR=0.104; p=0.003). In 2021, mental health was associated only with sleep change (OR=3.522; p=0.035). Conclusion: The impact of mental health symptoms on sleep quality of PAD patients was attenuated along the coronavirus pandemic.